Nigerian Mass Media and Cultural Status Inequalities: A Study among Minority Ethnic Groups - Ojebode, Ayobami; Onekutu, Patience (Technium Social Sciences Journal, 2021)
What the mass media do to the cultures of peoples has been an object to which much scholarly and policy attention has been devoted. In Africa, the media have been called upon to be active agents in nation building, cultural integration and development. However, as they attempt to perform these functions, the media elevate the cultural practices of some groups above those of others thereby creating cultural status inequalities. In this study, we attempted to explore the extent to which this was true in the Nigerian situation. Working among six minority ethnic groups and on data sourced through four different methods, we discovered that there is wide cultural status inequalities fostered by the mass media. The media devote minute attention to the minority groups. Only 23% of print and 6.3% of broadcast content analysed were devoted to the over 350 minority groups in Nigeria. Of this negligible coverage, 69% was negative coverage. About 81% of our respondents had never seen their language written in a newspaper; over 65% had not heard their language spoken on television. Almost all of their festivals and cultural activities are not covered by television or newspaper or news magazines whereas those of the majority groups are. Unlike the majority groups, in most cases, the minorities are invisible in the content of the media except when they do something negative. Our respondents felt marginalized over this. They affirmed a link between their invisibility and other forms of inequalities. The study recommends policy directions that can help redress the wide cultural status inequalities. Keywords: Cultures, Inequalities, Mass media, Minority Ethnic groups